The impact of global selection on local adaptation and reproductive isolation - Bisschop, Gertjan; Setter, Derek; Rafajlović, Marina; Baird, Stuart J E; Lohse, Konrad (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2020)
Despite the homogenizing effect of strong gene flow between two populations, adaptation under symmetric divergent selection pressures results in partial reproductive isolation: adaptive substitutions act as local barriers to gene flow, and if divergent selection continues unimpeded, this will result in complete reproductive isolation of the two populations, i.e. speciation. However, a key issue in framing the process of speciation as a tension between local adaptation and the homogenizing force of gene flow is that the mutation process is blind to changes in the environment and therefore tends to limit adaptation. Here we investigate how globally beneficial mutations (GBMs) affect divergent local adaptation and reproductive isolation. When phenotypic divergence is finite, we show that the presence of GBMs limits local adaptation, generating a persistent genetic load at the loci that contribute to the trait under divergent selection and reducing genome-wide divergence. Furthermore, we show that while GBMs cannot prohibit the process of continuous differentiation, they induce a substantial delay in the genome-wide shutdown of gene flow. This article is part of the theme issue 'Towards the completion of speciation: the evolution of reproductive isolation beyond the first barriers'.
Keywords: reprodukční izolace; Models, Genetic; gene flow; Adaptation, Biological; modely genetické; selekce (genetika); Reproductive Isolation; ecological speciation; local adaptation; Selection, Genetic; divergent selection; Gene Flow; biologická adaptace; reproductive isolation; tok genů